Are teachers “butter lamps”? Teacher stress in Chinese Minzu “ethnic” schools - Sude, Bilige; Dervin, Fred; Yuan, Mei; Chen, Ning (Frontiers in Psychology, 2023)
China is a unified multi-ethnic country. Although research on teacher stress is plentiful in this context, the specific case of Minzu (“ethnic”) teachers is under-researched. Using Minzu schools located in a diverse county of the Inner Mongolia Autonomous Region (North China), as a case study, the authors examine factors behind Minzu teacher stress. Using mixed methods, three main results were identified by analyzing interviews and questionnaires with both the software NVivo and dialogical discourse analysis: societal, school and Self factors. In general, the teachers confirmed that their job was extremely stressful. While some of these aspects derived directly from the specific context of Minzu education (e.g., rural and pastoralist families send their children to towns leading to teachers taking over parents’ responsibilities), some elements were also found in other contexts of Chinese education and/or internationally. The article ends with some recommendations specifically about Minzu aspects in the treatment of teacher stress, which will also be of interest for international audiences.